Linking operation parameters and environmental variables to population dynamics of Mycolata in a membrane bioreactor. (March 2015) - Maza-Márquez, P.; Gómez-Silván, C.; Gómez, M.A.; González-López, J.; Martínez-Toledo, M.V.; Rodelas, B.
Graphical abstract: Highlights: Mycolata community structure changes were analyzed in a long-term operated MBR. The dynamics of total and active populations were monitored by TGGE fingerprinting. Phylotypes were related to Gordonia, Mycobacterium, Rhodococcus and Segniliparus . Population dynamics were 30–32% explained by changes of BOD5, iTSS and VSS. Foaming was connected to the abundance of Mycolata unrelated to Gordonia amarae . Abstract: The community structure and population dynamics of Mycolata were monitored in a full-scale membrane bioreactor during four experimental phases under changing operating and environmental conditions, by means of temperature-gradient gel electrophoresis of partial 16S-rRNA genes amplified from community DNA and RNA templates (total and active populations). Non-metric multidimensional scaling and BIO-ENV analyses demonstrated that population dynamics were mostly explained (30–32%) by changes in the input of nutrients in the influent water and the accumulation of biomass in the bioreactors, while the influence of hydraulic and solid retention times, temperature and F/M ratio was minor. Significant correlations were observed between particular Mycolata phylotypes and one or more variables, contributing information for the prediction of their abundance and activity under changing conditions. Fingerprinting and multivariate analyses demonstrated that two foaming episodes, recorded at temperatures <20 °C, were connected to the increase of the relative abundance of Mycolata unrelated to Gordonia amarae .